2013
DOI: 10.1039/c3cp44448a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions of Alzheimer amyloid-β oligomers with neutral and negatively charged lipid bilayers

Abstract: Interaction of p3 (Aβ17-42) peptides with cell membrane is crucial for the understanding of amyloid toxicity associated with Alzheimer’s disease (AD). Such p3-membrane interactions are considered to induce the disruption of membrane permeability and integrity, but the exact mechanisms of how p3 aggregates, particularly small p3 oligomers, induce receptor-independent membrane disruption are not yet completely understood. Here, we investigate the adsorption, orientation, and surface interaction of the p3 pentame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 81 publications
(171 reference statements)
2
52
0
Order By: Relevance
“…These results indicate that electrostatic interaction is an important driving force to facilitate the adsorption on the anionic membrane. This finding is consistent with previous studies showing that electrostatic interactions with negatively charged lipids enhance peptide adsorption onto lipid monolayers/bilayers 45, 72 . The relative higher membrane binding probabilities of the residues in the N-terminal β 1 region also suggest strong interactions between N-terminal residues of Aβ trimers and POPG bilayers.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These results indicate that electrostatic interaction is an important driving force to facilitate the adsorption on the anionic membrane. This finding is consistent with previous studies showing that electrostatic interactions with negatively charged lipids enhance peptide adsorption onto lipid monolayers/bilayers 45, 72 . The relative higher membrane binding probabilities of the residues in the N-terminal β 1 region also suggest strong interactions between N-terminal residues of Aβ trimers and POPG bilayers.…”
Section: Resultssupporting
confidence: 94%
“…Brown et al reported that the binding of disordered Aβ 1–42 tetramers on POPC membranes resulted in a greater membrane perturbation than that on cholesterol-rich membranes 47 . Multiple 80-ns MD simulations by Yu et al showed that the interactions of protofibrillar Aβ 17–42 pentamers with a mixed POPC and POPG membrane are stronger than those with POPC membranes 45 , indicative of the role of surface charge in Aβ-membrane interactions. Recently, Tofoleanu et al explored the influence of chemical compositions of POPC and POPE headgroups on the interactions of Aβ 9–40 protofilaments with membranes by performing MD simulations ranging from 25–150 ns.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that the tighter PC polar headgroup packing in the PC/PS bilayer provides a less conformationally favorable binding surface to the charged residues of the protein when compared to the relatively looser PC polar headgroup packing in the PC bilayer. Weak binding of a beta-amyloid p3 pentamer, which contains identical C -terminal domains as in this work but no N -terminal domains on the same mono-unsaturated PC as used in this work, has been reported (Yu et al, 2013). However, another binding study using the same beta-amyloid p3 pentamer, but on membrane surfaces of unsaturated PC, i.e.,18:1 in both sn -1 and sn -2, reported strong protein surface binding.…”
Section: Discussionmentioning
confidence: 75%
“…Electrostatic interactions between the charged residues of the protein and lipid polar headgroups have been proposed to drive the initial membrane surface binding of beta-sheet rich beta-amyloid oligomers in various bilayer systems (Davis and Berkowitz, 2010; Jang et al, 2013; Yu et al, 2013; Tofoleanu et al, 2015). Those studies investigated single- and multiple-component lipid bilayers consisting of PC, PS, phosphatidylethanolamine (PE), and phosphatidylglycerol (PG) of different acyl chain compositions.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, it is considered that oligomers have a higher toxicity level compared with either monomers or fibrils (1,(51)(52)(53)(54). In addition, different high-resolution fibrillar structures might also possess variable levels of toxicity (32,33,55,56).…”
Section: Discussionmentioning
confidence: 99%